Speaking Out: Housing Issues of Youth in Nunavik - Ikey, Olivia (Études Inuit Studies, 2020)
Conference retranscription “Living in Northern Quebec,” special session “Arctic Housing and Community Planning” organized by Mylène Riva and Geneviève Vachon. Arctic Change 2017 Conference, Quebec City, Convention Centre, December 14th, 2017. Retransciption de la conférence « Habiter le Nord québécois », session « Logement et plannification communautaire dans l’Arctique », organisé par Mylène Riva et Geneviève Vachon. Congrès Arctic Change 2017, Québec, Centre des Congrès, 14 décembre 2017.